Hierarchically porous nanosheets-constructed 3D carbon network for ultrahigh-capacity supercapacitor and battery anode. (13th March 2019) - Wang, Ying-Ying; Hou, Bao-Hua; Ning, Qiu-Li; Pang, Wei-Lin; Rui, Xian-Hong; Liu, Mingkai; Wu, Xing-Long
Abstract: An advanced hierarchically porous nanosheets-constructed three-dimensional (3D) carbon material (HPNSC) is prepared by using low-cost agricultural waste-nelumbium seed-pods as the precursor, and potassium hydroxide (KOH) as the activator. The as-prepared HPNSC material has a hierarchically porous nanosheets-constructed structure with 3D carbon nanosheet network morphology, which can enable fast and efficient transfer of Li + /Na + /H + during charge–discharge process. The assembled HPNSC//HPNSC symmetric supercapacitors exhibit an improved energy density of 41.3 W h kg −1 with a power density of 180 W kg −1 in 1 mol l −1 Na2 SO4 electrolyte. The energy density can still be maintained at 16.3 W h kg −1 even if the power density is increased to 9000 W kg −1 . When acting as the reversible electrode for lithium ion batteries, this HPNSC material can achieve a high specific capacity of 1246 mA h g −1 at 0.1 A g −1 . Moreover, sodium ion battery with HPNSC electrode exhibits excellent cycling performance of 161.8 mA h g −1 maintained even after being cycled 3350 times. The electrochemical performances clearly indicate that the HPNSC developed in this work is a very promising energy storage electrode material, and can further provide new insights for designing and developing highly porous materials for energy storage in other fields.